PENGARUH KONSENTRASI SERBUK MAJEMUK BIJI SARIKAYA DAN BIJI SIRSAK TERHADAP MORTALITAS KUMBANG BERAS Sitophilus Oryzae L. (COLEOPTERA : CURCULIONIDAE) DI PENYIMPANAN - Lihawa, Zein; Toana, Moh. Hibban (AGROTEKBIS, 2017)
This research aims to determine the effect of compound seed powder sugar apple and soursop seed against S. oryzae mortality in storage. The study was conducted from January to April 2016 at the Laboratory of Plant Pests and Diseases Departement, Faculty Agriculture, Tadulako University Palu. Materials used seeds soursop (Annonamuricata L.) seeds and sugar apple seeds (Annonasquamosa L.), aquadestand local varieties of rice. The study design using a completely randomized design consisting of 6 treatments with 3 replications level namely P0: Control without giving samples; P1: 1g/200g of rice; P2: 2g/200g of rice; P3: 3g/200g of rice; P4: 4g/200g of rice); P5: 5g/200g of rice. The analysis uses a test of variance and to determine the best treatment to use honest significant difference test ? level of 0.05. The results showed that the compound powder sugar apple seed and seed soursop affect the rice beetles mortality. The most effective concentration causing mortality in rice beetles that is on the treatment of P2 concentration of 2g/200g of rice with a percentage of56.67%.The concentration was significantly different with the treatment of P3, P4, P5 each concentration 3g/200g, 4g/200g, 5g/200g rice with percentage mortality 81.11%, 92.22%, and 100.00% respectively. Key Words: Mortality, seed soursop powder and seed sugar apple powder, Sitophilus oryzae L.